An Overview of the Use of Absolute Dating Techniques in Ancient Construction Materials - Jorge Sanjurjo-Sánchez (Geosciences, 2016)
The reconstruction of the chronology of historical buildings is a tricky issue, as usually there are not historical documents that allow the assessment of construction phases, and some materials are hardly reliable for the use of dating techniques (e.g., stone). However, in the last two decades, important advances on the use of absolute dating methods on building materials have increased the possibilities of reconstructing building chronologies, although some advances are still scarcely known among archaeologists and architects. Recent studies performed on several kinds of mortars, fired bricks, mud-bricks, and even stone surfaces have shown that it is possible to date them. Both radiocarbon and luminescence dating have been the most frequently used techniques but others such as archaeomagnetism can also be used in some cases. This paper intends to give an overview of the recent achievements on the use of absolute dating techniques for building materials.